PEMANFAATAN KONSENTRAT PROTEIN IKAN (KPI) PATIN DALAM PEMBUATAN BISKUIT - Nuri Arum Anugrahati; Joko Santoso; Indra Pratama (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2012)
Biscuits are classified as cereal-based food products made from wheat flour or other flours. Addition of Fish Protein Concentrate (FPC) in biscuits was expected to produce biscuits with higher protein content and better characteristics. The objective of this research was to determine the concentration of FPC of patin fish in biscuit making. FPC concentration was added at 10-25% (w/w) of the total formula of biscuits. Determination of the best concentration of KPI based on the biscuit parameters of organoleptic and physical tests. Biscuits with 20% FPC had color and aroma similar to control biscuit. The control biscuits taste, crispiness, and hardness were similar to biscuits with 15% FPC. The best concentration of KPI added in biscuit was 15% of the total of formula biscuits. Biscuit with 15% KPI had higher levels of protein and the digestibility of proteins in vitro was higher than the control.Keywords: biscuit, fish protein concentrate, patin fish, crispiness